Effects of Wollastonite on Selected Properties of Medium-Density Fiberboards Made from Wood and Palm Leaf Residues - Hamid R. Taghiyari; Mahdi Arabi; Petar Antov; Elham Nadali; Dorina C. Ilies; Ehsan Salimifard; Ismaeil Shishegar; Viktor Savov; Viktoria Dudeva; Jakub Kawalerczyk; Mariana Ratiu (BioResources)
Effects of adding wollastonite (W, at 5% and 10%) and palm leaf residues(at 10%), based on the dry weight of wood fibers, were evaluated relative to selected properties of medium-density fiberboards (MDF), bonded with two adhesive systems, i.e., urea-formaldehyde (UF, at 10%) and isocyanate (IC, at 5%) resins. The results indicated a general improvement in screw withdrawal resistance in the UF-bonded panels due to the addition of wollastonite. This enhancement is attributed to the reinforcing effect of wollastonite. In the IC-bonded panels, the addition of wollastonite had an improving effect when W-content was 5%. The addition of defibrated palm leaves generally decreased the screw withdrawal resistance of the MDF panels due to the soft nature of the palm fibers. The fire properties of the IC-bonded panels tended to be more favorable or at least comparable to those of the UF-bonded panels, which was attributed to the formation of bubbles in the cured resin. The addition of wollastonite generally improved fire properties in both resins. It was concluded that wollastonite and defibrated palm leaves can be recommended for MDF production when the contents of wollastonite and palm leaves do not exceed 5% and 10%, respectively.